P-50 Collaboration and networking: developing the palliative medicine SAS doctor workforce in the north west. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Hodgson, Aruna; Waterman, David; Bonwick, Helen
Abstract : Background: The Palliative Medicine workforce is diverse, including consultants, SAS (staff grade, associate specialist and specialty) doctors, GPs and training grades. This project, funded by Greater Manchester and Eastern Cheshire Strategic Clinical Networks, was designed specifically to support the development of SAS doctors working in specialist palliative care in the region. It aimed to help address the challenge of ensuring that there are enough appropriately trained doctors to meet current and future service need. Aims and methods of the project: Mapping of numbers of doctors working in Palliative Medicine in SAS grade or similar posts across the region; Survey of career aspirations and development needs of doctors working in SAS grade or similar posts; Holding networking/educational events for SAS doctors; Producing a training and development framework for doctors working in SAS grade or similar roles who wish to progress in their careers. Results: All elements of the project have been achieved and the Training and Development Framework was launched in May 2019. Details of the mapping, the survey of development needs and the educational events will be shared. The project has benefited hugely from collaborative working with colleagues in Cheshire and Merseyside, who had already developed and implemented a Training and Development Programme for SAS doctors in their region. Conclusion: It was evident that providing the opportunity for SAS doctors to network with colleagues from other hospices and palliative care teams was particularly valuable, and has led on to the development of peer-led initiatives such as a Medical Directors Forum and a WhatsApp group. Further work to embed the Training and Development Framework and further support SAS doctor development in the region is currently being planned.